ANTIBACTERIAL EFFECT OF TITANIUM DIOXIDE NANOPARTICLES AND CHITOSAN NANOPARTICLES IN ORTHODONTIC ADHESIVE RESIN ON STREPTOCOCCUS MUTANS COLONY - Wulandani Liza Putri; Erwin Siregar; Haru Setyo Anggani (FKG Unlam, 2021)
ABSTRACTBack ground:Strepococcus mutans colonization around orthodontic bracket is the common thing that may commence the development of white spot lesion.Objectives: This research is to analyze antibacterial effect of titanium dioxide nanoparticles and chitosan nanoparticles in orthodontic adhesive resin toward Streptococcus mutans colony. Methods: This research was conducted at RSKGM University of Indonesia on August 2019. Thirty extracted premolars were randomly allocated into three groups. Bracket was bonded to each specimen using orthodontic adhesive resin (Transbond XT) that was incorporated with titanium dioxide/chitosan nanoparticles. Each sample was submerged in bacterial suspension and was incubated for 24 hours. Streptococcus mutans colony around orthodontic bracket was counted with Total Plate Count methodandthen analyzed using statistical analysis. Results: There is no difference in Streptococcus mutans colony around orthodontic brackets among three treatment groups. Conclusion: Antibacterial effect of orthodontic adhesive resins incorporated with titanium dioxide nanoparticles did not differ from orthodontic adhesive resins incorporated with or without chitosan nanoparticles. This is depicted from the number of Streptococcus mutans colonies around the orthodontic brackets.Keywords: Chitosan nanoparticles, Orthodontic adhesive resin, Streptococcus mutans, Titanium dioxide nanoparticles